Akuntansi dan Tanggung Jawab Sosial: Telaah Normatif atas Hilangnya Makna Etis Transparansi dan Akuntabilitas - Hariatih; Hamid Habbe, Abdul; Pagalung, Gagaring (Bongaya Journal of Research in Accounting (BJRA), 2025)
This article examines the role of accounting as a means of social justice through a normative approach that emphasizes the importance of ethical values, social responsibility, and the principle of fairness in reporting practices. Amidst increasing demands for transparency and accountability, contemporary accounting reporting often loses its ethical meaning due to the dominance of technocratic and symbolic approaches. By referring to John Rawls' theory of justice, legitimacy theory, and critical accounting theory, this article highlights how market-oriented reporting tends to ignore the interests of the public and vulnerable groups. The research was conducted non-empirically through literature studies and argumentative-conceptual analysis of reporting practices in Indonesia and globally. The results of the study indicate that a fair reporting system must be designed in a participatory, inclusive, and social value-based manner, and integrate the ethics of the accounting profession as a moral agent in society. This article recommends the reformulation of reporting standards and the strengthening of professional ethics education to address the challenges of information justice and social responsibility in accounting.